Integration by Parts

A LevelAQAEdexcelOCR

Integration by Parts Revision

Integration by Parts

We have already seen the reverse chain rule. Integration by parts is the reverse product rule.

Integration by parts has many uses, most notably integrating things of the form x^{n}f(x).

For some questions, you need to integrate by parts more than once to get a result.

A LevelAQAEdexcelOCR

Integration by Parts

Recall: The product rule.

\dfrac{d}{dx}(uv)=u\dfrac{dv}{dx}+v\dfrac{du}{dx}

Integration by parts is the reverse of this.

{\LARGE \int}u\dfrac{dv}{dx}=uv-{\LARGE \int}v\dfrac{du}{dx}

You should choose u to be something that differentiates nicely, so that you can evaluate the integral on the right-hand side.

Example: Find \int x\sin(x)dx

u=x\;\;\;\dfrac{dv}{dx}=\sin(x)

\dfrac{du}{dx}=1\;\;\;v=-\cos(x)

\begin{aligned}\int x\sin(x)dx&=-x\cos(x)-\int-\cos(x)dx\\[1.2em]&=-x\cos(x)+\int \cos(x)dx\\[1.2em]&=-x\cos(x)+\sin(x)+c\end{aligned}

A LevelAQAEdexcelOCR

Integral of the Natural Logarithm

One of the most important uses of integration by parts is that it gives us a way to find \int \ln(x)dx, by writng \ln(x) as
1\times \ln(x).

u=\ln(x)\;\;\;\dfrac{dv}{dx}=1

\dfrac{du}{dx}=\dfrac{1}{x}\;\;\;v=x

\begin{aligned}\int \ln(x)dx&=x\ln(x)-\int x\dfrac{1}{x}dx\\[1.2em]&=x\ln(x)-\int1dx\\[1.2em]&=x\ln(x)-x+c\\[1.2em]&=x(\ln(x)-1)+c\end{aligned}

A LevelAQAEdexcelOCR

Integrating by Parts Multiple Times

Some integrals require you to integrate by parts multiple times to get a solution to.

Example: Find \int x^{2}e^{x}dx

u=x^{2}\;\;\;\dfrac{dv}{dx}=e^{x}

\dfrac{du}{dx}=2x\;\;\;v=e^{x}

\begin{aligned}\int x^{2}e^{x}dx=x^{2}e^{x}-\int2xe^{x}dx\end{aligned}

We must integrate by parts again the second integral.

u=2x\;\;\;\dfrac{dv}{dx}=e^{x}

\dfrac{du}{dx}=2\;\;\;v=e^{x}

\begin{aligned}\int x^{2}e^{x}dx&=x^{2}e^{x}-2xe^{x}+\int2e^{x}dx\\[1.2em]&=x^{2}e^{x}-2xe^{x}+2e^{x}+c\end{aligned}

A LevelAQAEdexcelOCR

Integration by Parts Example Questions

u=2x\;\;\;\dfrac{dv}{dx}=e^{3x}

 

\dfrac{du}{dx}=2\;\;\;v=\dfrac{1}{3}e^{3x}

 

\begin{aligned}\int 2xe^{3x}dx&=\dfrac{2}{3}xe^{3x}-\int\dfrac{2}{3}e^{3x}dx\\[1.2em]&=\dfrac{2}{3}xe^{3x}-\dfrac{2}{9}e^{3x}+c\end{aligned}

Have that \int \ln(x)dx=x(\ln(x)-1)+c

 

The 4 will remain at the front, and the 5 inside the function becomes a \dfrac{1}{5} at the front when integrating.

 

\begin{aligned}\int 4\ln(5x)dx&=4\times\dfrac{1}{5}\times 5x(\ln(5x)-1)+c\\[1.2em]&=4x(\ln(5x)-1)+c\end{aligned}
u=x^{3}\;\;\;\dfrac{dv}{dx}=\cos(2x)

 

\dfrac{du}{dx}=3x^{2}\;\;\;v=\dfrac{1}{2}\sin(2x)

 

\begin{aligned}\int x^{3}\cos(2x)dx=\dfrac{1}{2}x^{3}\sin(2x)-\int\dfrac{3}{2}x^{2}\sin(2x)dx\end{aligned}

 

Integrate the integral on the right-hand side by parts.

 

u=\dfrac{3}{2}x^{2}\;\;\;\dfrac{dv}{dx}=\sin(2x)

 

\dfrac{du}{dx}=3x\;\;\;v=-\dfrac{1}{2}\cos(2x)

 

\begin{aligned}\int x^{3}\cos(2x)dx&=\dfrac{1}{2}x^{3}\sin(2x)+\dfrac{3}{4}x^{2}\cos(2x)-\int\dfrac{3}{2}x\cos(2x)dx\end{aligned}

 

Use integration by parts again.

 

u=\dfrac{3}{2}x\;\;\;\dfrac{dv}{dx}=\cos(2x)

 

\dfrac{du}{dx}=\dfrac{3}{2}\;\;\;v=\dfrac{1}{2}\sin(2x)

 

\begin{aligned}\int x^{3}\cos(2x)dx&=\dfrac{1}{2}x^{3}\sin(2x)+\dfrac{3}{4}x^{2}\cos(2x)-\dfrac{3}{4}x\sin(2x)+\int\dfrac{3}{4}\sin(2x)dx\\[1.2em]&=\dfrac{1}{2}x^{3}\sin(2x)+\dfrac{3}{4}x^{2}\cos(2x)-\dfrac{3}{4}x\sin(2x)-\dfrac{3}{8}\cos(2x)+c\end{aligned}

Additional Resources

MME

Exam Tips Cheat Sheet

A Level
MME

Formula Booklet

A Level

You May Also Like...

MME Learning Portal

Online exams, practice questions and revision videos for every GCSE level 9-1 topic! No fees, no trial period, just totally free access to the UK’s best GCSE maths revision platform.

£0.00
View Product